2004
DOI: 10.1110/ps.04831804
|View full text |Cite
|
Sign up to set email alerts
|

Sonication of proteins causes formation of aggregates that resemble amyloid

Abstract: Despite the widespread use of sonication in medicine, industry, and research, the effects of sonication on proteins remain poorly characterized. We report that sonication of a range of structurally diverse proteins results in the formation of aggregates that have similarities to amyloid aggregates. The formation of amyloid is associated with, and has been implicated in, causing of a wide range of protein conformational disorders including Alzheimer's disease, Huntington's disease, Parkinson's disease, and prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
243
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(257 citation statements)
references
References 72 publications
11
243
0
3
Order By: Relevance
“…In one particular study, a range of structurally diverse protein systems including BSA, myoglobin, lysozyme, Tm0979, SOD and hisactophin were shown to generate amyloid like structures following sonication. 76 Shear effects on protein aggregation have also been studied in uniform flow fields. For example, a shear-induced nucleation, without flow enhanced aggregation, of preheated b-lactoglobulin solutions (0.5 wt%) at low pH has been reported.…”
Section: Protein Aggregationmentioning
confidence: 99%
“…In one particular study, a range of structurally diverse protein systems including BSA, myoglobin, lysozyme, Tm0979, SOD and hisactophin were shown to generate amyloid like structures following sonication. 76 Shear effects on protein aggregation have also been studied in uniform flow fields. For example, a shear-induced nucleation, without flow enhanced aggregation, of preheated b-lactoglobulin solutions (0.5 wt%) at low pH has been reported.…”
Section: Protein Aggregationmentioning
confidence: 99%
“…The first paper suggesting the usefulness of ultrasonication for amyloid nucleation was by Stathopulos et al 34) They showed that, for various proteins (i.e., bovine serum albumin, horse heart myoglobin, hen egg white lysozyme, Tm0979, recombinant hisactophilin, and human cytosolic Cu/Zn superoxide dismutase), ultrasonication results in the formation of amyloid-like aggregates. They suggested that protein unfolding and aggregation are caused by the ultrasonication at the water-air interface of cavitation bubbles, leading to the amyloid nucleation.…”
Section: Amyloid Fibrillation At Low Phmentioning
confidence: 99%
“…Stathopulos et al 34) showed that ultrasonication results in the formation of amyloid-like aggregates. Subsequently, amyloid fibrillation of various proteins such as -synuclein, 52) 2-m, 53) transthyretin, 54) and mouse prion proteins 50) was reported to be accelerated by ultrasonic irradiation.…”
Section: Mechanism Of Ultrasonication-triggered Fibrillation and Futumentioning
confidence: 99%
“…The majority of assays used for inhibitor identification apply dye-binding protocols that differentiate between free dye and dye bound to peptide aggregates by measuring spectral shifts. These dyes bind to peptide aggregates by non-specific, hydrophobic interactions and are unable to discern between low-versus highmolecular weight aggregates [53][54][55][56][57][58]. This has become of concern since recent studies suggest that the early stages of peptide oligomerization forming low-molecular weight aggregates may represent the most toxic form in vivo [7,9,10,59].…”
Section: Discussionmentioning
confidence: 99%